Development Design of a Compact Pulsed Electric Field to Reduce Food Bacteria: Laboratory Scale - Darmawan, Arry; Wulandari, Nur; Kusumaningrum, Harsi Dewantari; Nurjanah, Siti; Sugiarto, Anto Tri; Qirom, Qirom; Parikesit, Adji; Unadi, Astu; Sabirin, Sabirin (Engineering, Technology & Applied Science Research, 2025)
This study aims to design a high-efficiency Pulsed Electric Field (PEF) device for bacterial inactivation in food at a laboratory scale. Bacterial inactivation is closely affected by the consistency, intensity, and duration of the applied electric field; thus, although multiple circuit topologies can be employed in PEF devices, not all provide compactness and efficiency. For this study, an iterative design approach was used to evaluate solid-state cascade PEF topologies by comparing transformer-based (2 A and 5 A) and ignition coil-based (mini-cylinder, cylinder, and canister) configurations. The results show that PEF devices employing a 2 A transformer current and a mini-cylindrical ignition coil offer superior reliability and compactness, making them suitable for treating liquid, semi-solid, and solid samples. Experimental validation of the PEF effect on bacterial membrane damage, using the Vibrio parahaemolyticus strain, demonstrated that an electric field intensity of 10.5 kV/cm caused significant cell damage. Extended treatment durations led to progressively higher bacterial mortality (p < 0.05), as confirmed by flow cytometry and Scanning Electron Microscope (SEM) observations of cell morphology. Therefore, this study successfully developed a PEF device that potentially replaces the traditional Pulse Forming Network (PFN) with a mini-cylindrical ignition coil, thereby improving replicability and accessibility for laboratory-scale applications.